Bibliometric Analysis and Preliminary Diversity Assessment of the Genus Dillenia in Sulawesi - Andhika Senatama; Melya Riniarti; Inggar Damayanti; Irfan Martiansyah; Prima Wahyu Kusuma Hutabarat (Forest and Nature, 2025)
The genus Dillenia (Dilleniaceae) comprises approximately 100 species distributed across South Asia, Southeast Asia, and northern Australia. In Indonesia, research on Dillenia remains limited, particularly regarding updated data on its diversity and distribution. This research aims to know the research gap of the genus Dillenia globally and inventory Dillenia collection from Sulawesi at Herbarium Bogoriense (BO) and Bogor Botanical Garden (BBG). This study first conducted a bibliometric analysis using data from the Scopus database, followed by a descriptive approach through morphological observation of herbarium specimens from Sulawesi deposited in the BO and living collections in the BBG. The bibliometric analysis revealed five major research clusters in Dillenia studies: antibacterial activity and phytochemistry; ethnobotany and traditional uses; pharmacology and cytotoxicity; phytochemical analysis and plant extracts; and compound isolation and purification. Research on taxonomy, ecology, and conservation of Dillenia remains underexplored and offers substantial opportunities for further investigation. The inventory confirmed the presence of four endemic species in Sulawesi—D. serrata, D. ochreata, D. celebica, and D. talaudensis—and D. pentagyna, which is more broadly distributed. However, potential misidentification was observed in some specimens, notably the occurrence of D. ptempoda in the BBG collection, a species not listed in previous taxonomic revisions.